Patient sex and use of tranexamic acid in liver transplantation - Dehne, Sarah; Jackson Gil, Lorena; Riede, Carlo; Feißt, Manuel; Mehrabi, Arianeb; Michalski, Christoph; Weigand, Markus A.; Decker, Sebastian; Larmann, Jan (Frontiers in medicine, 2024)
Background Differences in medical treatment between women and men are common and involve out-of-hospital emergency care, the intensity of pain treatment, and the use of antifibrinolytic treatment in emergency trauma patients. If woman and man receive different antifibrinolytic treatment in highly-standardized major transplant surgery is unknown. Methods We conducted a retrospective cohort study on patients who underwent liver transplantation at Heidelberg University Hospital, Heidelberg, Germany between 2004 and 2017. Logistic regression analyses were performed to determine if sex is associated with the administration of TXA during liver transplantation. Secondary endpoints included venous thrombotic complications, graft failure, mortality, myocardial infarction, hepatic artery thrombosis, and stroke within the first 30 days after liver transplant as well as length of hospital stay and length of intensive care unit stay. Results Out of 779 patients who underwent liver transplantation, 262 patients received TXA. Female sex was not associated with intraoperative administration of TXA [adjusted OR: 0.929 (95% CI 0.654; 1.320), p = 0.681]. The secondary endpoints graft failure (13.2% vs. 8.4%, women vs. men, p = 0.039), pulmonary embolism (3.4% vs. 0.9%, women vs. men, p = 0.012), stroke (1.7% vs. 0.4%, women vs. men, p = 0.049), and deep vein thrombosis (0.8% vs. 0%, women vs. men, p = 0.031) within 30 days after liver transplantation were more frequent in women. Mortality, myocardial infarction, and other secondary endpoints did not differ between groups. However, in women, the use of TXA was associated with a lower rate in thromboembolic complications. Conclusion Our data indicate that different from other scenarios with massive bleeding complications the administration of TXA during liver transplantation is not associated with sex. However, sex is associated with the risk for complications, and in woman TXA might have a preventive effect on the rate of thromboembolic complications. Reasons underlying the observed sex bias rate remain uncertain.
Gesehen am 26.11.2024